PERAN GURU AL-QUR’AN HADITS TERHADAP PESERTA DIDIK YANG KESULITAN MEMBACA AL-QUR’AN DI KELAS VII MTs AL-MA’MUR BANJARSARI TANGGAMUS - Devi Sela Eka Selvia; Elva Fauziah; Misdarwati; Ruswanto; Nana Sofiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This Research "The Role of Al-Qur'an Hadith Teachers Towards Students Who Have Difficulty Reading the Qur'an at MTs Al-Ma'mur Banjarsari Tanggamus". This study aims to determine the role of Al-Qur'an Hadith teachers in overcoming students who have difficulty reading the Qur'an in class VII MTs Al-Ma'mur Banjarsari Tanggamus. The background of this study is that there are still many students who are not able to read the Qur'an properly, especially in terms of pronouncing the hijaiyah letters and applying the laws of tajwid. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that Al-Qur'an Hadith teachers have a very important role, not only as teachers but also as guides, motivators, and facilitators. Teachers use various strategies such as providing motivation, creating a comfortable learning atmosphere, providing remedial learning, using varied learning media, and conducting periodic evaluations to improve student abilities. The obstacles faced include limited time, learning facilities, and differences in student ability levels. However, teachers are able to overcome these obstacles with an individual approach and methods that are tailored to student characteristics. In conclusion, the active role of Al-Qur'an Hadith teachers is very influential in helping students overcome difficulties in reading the Qur'an, thus supporting the achievement of Islamic education goals in forming a generation that is knowledgeable and has noble character.